DETERMINANASI KUALITAS AUDIT LAPORAN KEUANGAN PEMERINTAH DAERAH DENGAN MENGGUNAKAN PERSPEKTIF KARAKTERISTIK PEMERINTAH DAERAH DAN AUDITOR - MAHAMERU ROSY ROCHMATULLAH; RUDY HARTANTO; DWI RAHAYU (STIE Atma Bhakti, 2015)
This study discusses about audit quality of Local Government Financial Statements in Indonesia. This study aims to analyze the determinant audit quality of Local Government Financial Statements in Indonesia, if it’s seen from the perspective of The Local Government’s and the auditors’ characteristics. This study uses multiple regression method to 393 districts/ municipalities as a sample selected by purposive sampling method. The result showed that the characteristics of Local Government consisting of the size and complexity of Local Government, then the auditors’ characteristics consisting of the auditor’s professional proficiency, all three impact on the audit quality of Local Government Financial Statements. Further, the control variable comprising of Local Government Status and Geographic Types also affect audit quality of Local Government Financial Statements. However, the control variable of Local Government Types have no effect on audit quality. So these results prove that besides auditors themselves, the external factors such as the Local Government’s characteristics could also impact on the audit quality of Local Government Financial Statements in Indonesia. Keywords: Audit Quality, Auditors’ Characteristics, Auditor's Professional Proficiency,Local Government’s Characteristics, Local Government Complexity, Local Government Financial Statements,Local Government Geographical Types, Local Government Size, Local Government Types.